STRATEGI OPTIMALISASI PRODUKSI DAN PENDAPATAN UMKM KERIPIK PETAMPE SELAMA PANDEMI COVID-19 MELALUI PENCARIAN SUMBER AIR TAWAR, MANAJEMEN RANTAI PASOK KERIPIK PETAMPE, TTG MIXER DAN DOUGH SHEETER - Idon Joni; Sandy Vikki Ariyanto; Imron Rosyadi; Syaiful Anam; Fredy Yunanto (COVIT (Community Service of Health), 2023)
From the results of observations by the PKM TEAM, Local SMEs "IZZA PUTRI" (MITRA) are 1. Lack of fresh water to meet the needs of Petampe Chips production. 2. Haven't used the TTG Mixer tool to simplify and speed up the process of making Petampe Chips dough. 3. Haven't used the automatic TTG Dough Sheeter to speed up the process of flattening the Petampe Chips dough and adjusting the thin size of the Petampe Chips dough. 4. Packaging still needs a creative, innovative and modern touch. 5. Have not implemented Logistics Management and Supply Chain for Petampe Chips production. 6. Marketing is still local (offline) and has not implemented online marketing. The method used is a combination of knowledge possessed by students and the PKM Team as well as an approach guided by the principle that knowledge, technology and innovation to be received by partners must go through a process of listening, understanding, trying, evaluating, accepting, trusting and implementing. The results of this PKM are the ability to plan and analyze the development of Petampe Chips Production, as well as develop innovation both in the process and in the end results in a sustainable manner. Keywords: Optimization, MSME, Supply Chain Management